Colonic Metastasis of Adenoid Cystic Carcinoma 19 Years after the Primary Tumor Resection - Subramanya Sakaleshpura Mallikarjunappa; Shriram Jakate; Lin Cheng (Case Reports in Pathology)
Adenoid cystic carcinoma (ACC) is a tumor characterized by slow growth and late distant metastasis. The lung and breast are the most common sites for metastasis. Colonic metastasis of such a tumor is rare, with few case reports available. Here, we report a case of ACC arising from minor salivary gland that metastasized to the colon 19 years after the primary tumor resection, with literature review of the clinical, histological, and molecular features of ACC. This case raises our awareness of such tumors as a differential diagnosis of colorectal cancer.